An introduction to sociocultural anthropology: adaptations, structures, meanings - Haines, David W., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
A concise yet comprehensive guide to cultural anthropology using a materialist approach. This revised and updated edition exposes students to the cultural detail and personal experiences that lie in the anthropological record and extends their anthropological understanding to contemporary issues.--Provided by publisher.
1. The Anthropological Vision -- Part I. Adaptations. 2. Introduction to Part I -- 3. Foragers -- 4. Horticulturalists -- 5. Agriculturalists -- 6. Pastoralists -- 7. Industrialists -- Part II. Structures. 8. Introduction to Part II -- 9. Kinship: Terminology and Households -- 10. Kinship: Descent and Marriage -- 11. Economics -- 12. Politics -- 13. Religion -- Part III. Meanings. 14. Introduction to Part III -- 15. Cognition -- 16. Language -- 17. Expression -- 18. Action.
Second edition.
Keywords: Ethnology; Human geography; Ethnobiology